The complete mitochondrial genome of Loxosceles rufescens: an important medical species worldwide (Araneae: Sicariidae). Issue 1 (2nd January 2019) - Luo, Yufa; Fu, Dan
Abstract: Loxosceles rufescens, the Mediterranean recluse spider, is a cosmopolitan species with toxic venom which can cause skin lesions (arachnogenic necrosis) in humans. Here, the complete mitochondrial genome (mitogenome) was determined for L. rufescens (Sicariidae). It had a circular mapping organization with 15, 210 bp in length containing 13 protein-coding genes, two ribosomal RNA genes, 21 putative transfer RNA genes, and one control region. A Bayesian phylogenomic analysis of the representative species in Araneae showed that L. rufescens had a closer relationship with two species of Pholcidae and one species of Hypochilidae, which were the haplogyne spiders. The complete mitogenome will aid identification of L. rufescens, facilitate further genetic studies of the significant pest, and contribute to spider phylogenetic inferences.